Investment Limitation Between ASEAN and Non-ASEAN Countries in Presidential Regulation: Dimension of Non-Discrimination Principles - Purwanti, Ni Luh Putu Wulan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
Indonesia is bound by TRIMs agreements in terms of investment policies regarding goods trade and GATS regarding services trade. TRIMs and GATS as annexes of WTO agreements adhere to the non-discrimination principle namely MFN and NT. The difference in the percentage of the amount of capital that allowed to be owned in several business fields for a foreign investor to the investor from ASEAN and Non-ASEAN member countries is found in President Regulation No. 44/2016. Different treatment of non-ASEAN countries in the said Presidential Regulation whether it is a breach of the non-discrimination principle. It is deemed important to be investigated to know whether the investment regulations in Indonesia for the investors from ASEAN and Non-ASEAN countries have implemented the non-discrimination principle. Statutory and analytical of conceptual approach type in normative legal research were used in this writing. Indonesia as a developing country shall be included in the exemption by the WTO to make regulations which in this case give special treatment to ASEAN member countries as stipulated in Article 4 of the TRIMs and flexibility in implementing the non-discrimination principle referred to in Article 4 and 5 of GATS.